Analyses of multiple-site and concurrent Chlamydia trachomatis serovar infections, and serovar tissue tropism for urogenital versus rectal specimens in male and female patients. Issue 6 (19th August 2011) - Bax, C J; Quint, K D; Peters, R P H; Ouburg, S; Oostvogel, P M; Mutsaers, J A E M; Dörr, P J; Schmidt, S; Jansen, C; van Leeuwen, A P; Quint, W G V; Trimbos, J B; et al.
Abstract : Objectives: The aims of this study were: to determine the incidence of concurrent infections on a serovar level; to determine the incidence of multiple anatomical infected sites on a detection and genotyping level and analyse site-specific serovar distribution; to identify tissue tropism in urogenital versus rectal specimens. Methods: Chlamydia trachomatis -infected patients in two populations were analysed: 75 visiting the outpatient department of obstetrics and gynaecology of the MC Haaglanden, and 358 visiting the outpatient sexually transmitted disease clinic, The Hague, The Netherlands. The PACE 2 assay (Gen-Probe) was used to detect C trachomatis from urethral, cervical, vaginal, oropharyngeal and anorectal swabs. C trachomatis genotyping was performed on all C trachomatis positive samples, using the CT-DT genotyping assay. Results: Samples from 433 patients (256 female and 177 male) with confirmed C trachomatis infection were analysed. In 11 patients (2.6%), concurrent serovars in one anatomical sample site were present. In 62 (34.1%) female and four (9.3%) male patients, multiple sample site infections were found. A substantial percentage of women tested at the cervical/vaginal and rectal site were found to be positive at both sites (36.1%, 22/61). In men, D/Da and G/Ga serovars were more prevalent in rectal than urogenital specimens (p=0.0081 and p=0.0033, respectively), while serovar E was more prevalent in urogenital specimens (p=0.0012). Conclusions: The prevalence of multiple serovar infections is relatively low. Significant differences in serovar distribution are found in rectal specimens from men, with serovar G/Ga being the most prominent, suggesting tissue tropism.